Gobierno Abierto y educación en América Latina y el Caribe - Hevia, Felipe (El Colegio de México, 2021)
Open Government seeks to improve the provision of public services with transparency, accountability, and participation. Open Government Commitments in education in Latin America and the Caribbean are analyzed to determine whether they address substantive or accessory aspects of education policies. A corpus of 51 commitments was constructed between 2011 and 2016. They were analyzed and classified by country, subject and educational quality dimensions. Results: regional variation exists; commitments are concentrated in the dimensions of Internet access, education expenditure monitoring, “efficiency” and “equity.” The author considers the potential and limits of Open Government for increasing transparency, participation, and accountability in education and proposes a future research agenda.